The Power of Voice: Using Audio Podcasts to Teach Vocal Performance and Digital Communication - Amanda Hill (Central States Communication Association, 2021)
Today's students often speak through mediated technologies. Thus, understanding how nonverbal cues impact meaning-making is key to understanding effective communication across mediums. This case study explores a group project where students created audio podcasts to teach others about a specific aspect of communication studies while considering the way sound and vocal performance affect the transference of the message. This article examines the use of audio podcasts as a vehicle for teaching university students about the power of paralinguistic and chronemic nonverbal behaviors.